The Roma in Croatia: From Migration to Intercultural Relations - Neven Hrvatić (Migracijske i etničke teme, 2004)
From their first arrival in Croatia (in Dubrovnik in 1362), due to their transnational identity, the Roma have formed a historical ethnic community. A specific tribal system and economic backwardness determined their dispersion, specialisation, the partial loss of their ethnic identity and their marginal position. Based on empirical surveys carried out among secondary school students in Croatia, the scientific research projects: “Genealogy and the Transfer of Intercultural Models” and “The School Curriculum and the Traits of Croatian National Culture” (1991–2001), have revealed the existence of stereotypes in regard to the Roma, a low level of acceptance of elements of Roma culture (language, art, history, customs), as well as great social distance towards the Roma (through a modified Bogardus scale), which altogether indicates a need for intercultural education and schooling for all school pupils in Croatia. An improvement in their socio-economic situation and integration into all segments of society is crucial to the Roma national minority in Croatia, but there is likewise a need to preserve Roma culture, traditions and lifestyle, so that the Roma could become and/or remain a recognisable part of the multicultural milieu.